1982
DOI: 10.1056/nejm198202113060603
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-von Willebrand's Disease

Abstract: Four members (from four generations) of a family with a mild bleeding disorder and intermittent thrombocytopenia had decreased plasma levels of properties related to factor VIII/von Willebrand factor (FVIII/VWF), an absence of high-molecular-weight forms of FVIII/VWF in the plasma (but normal multimeric structure in the platelets), and increased ristocetin-induced platelet aggregation, as in Type IIB von Willebrand's disease. However, unlike the abnormality in FVIII/VWF in Type IIB disease, the basic defect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Variant forms ofvWd with enhanced RIPA have been described which show similar characteristics to those of our four patients, including the increased aggregation ofPRP to low-dose ristocetin, the altered multimeric structure of plasma vWf, and the occurrence of thrombocytopenia (1)(2)(3)(4)(5)(20)(21)(22)(23). Type Ilb vWd is described as a plasma abnormality, since the patients' plasma vWf binds to normal platelets at lower ristocetin concentrations than does normal vWf (1).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Variant forms ofvWd with enhanced RIPA have been described which show similar characteristics to those of our four patients, including the increased aggregation ofPRP to low-dose ristocetin, the altered multimeric structure of plasma vWf, and the occurrence of thrombocytopenia (1)(2)(3)(4)(5)(20)(21)(22)(23). Type Ilb vWd is described as a plasma abnormality, since the patients' plasma vWf binds to normal platelets at lower ristocetin concentrations than does normal vWf (1).…”
Section: Discussionsupporting
confidence: 78%
“…In pseudo-vWd or platelet-type vWd, the plasma vWf defect is secondary to a platelet abnormality that results in the adsorption of the largest multimeric forms of plasma vWf to platelets independent of ristocetin. Since the plasmas of these patients lack the largest multimers, platelet aggregation ensues only when normal vWfin the form ofcryoprecipitate or purified protein (possessing the largest multimers) is infused in vivo or added in vitro to their platelet-rich plasma (PRP) or when these multimeric forms are released in vivo after I-desamino-8-D-arginine vasopressin (DDAVP) infusion (2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…13). The latter is associated with platelet-type pseudo-von-Willebrand disease (14,15) and may be responsible for the enhanced interaction with plasma vWF typical of this congenital bleeding disorder (16). We found that beads coated with the 45-kDa GP Ib␣ domain behave like platelets in the interaction with immobilized vWF under flow conditions.…”
mentioning
confidence: 75%
“…This paradox may be resolved by considering that prolongation of the effective lifetime of the GP Ib␣-vWF bond caused by the G233V substitution may alter the association-dissociation equilibrium that normally permits soluble vWF and platelets to coexist in blood. Indeed, both clinical and experimental evidence suggest that circulating plasma vWF binds with enhanced affinity to platelets in patients with platelet-type pseudo-von-Willebrand disease (14)(15)(16). Thus, it is conceivable that the mutant receptor on circulating platelets, because of its heightened ligand-binding capacity, becomes blocked by plasma vWF and is consequently unable to interact with vascular surfaces when required for initiating hemostasis at sites of tissue injury (33).…”
Section: Discussionmentioning
confidence: 99%
“…These mutations increase the affinity of GPIb␣ for the vWF A1 domain so that binding occurs with a K d of Ϸ600 nM (24), without the need for a cofactor such as ristocetin (31,32). GPIb␣(G233V͞M239V) stimulated the cleavage of substrates A1A2*A3 (without urea) and A1A2A3 (with urea) (Fig.…”
Section: Figmentioning
confidence: 99%